Analysis of hydrodynamic (flow) and thermal pattern in Kranji reservoir - Lee, Anabel Ching Han. (2013)
Many studies have been carried out to determine the factors that can effectively control cyanobacterial blooms in lakes and reservoirs. Modeling software such as DYRESM-CAEDYM are often used to simulate the processes within the lakes so as to understand which factors significantly affect cyanobacteria growth. Hence, the objective of this report is to use DYRESM-CAEDYM to simulate Kranji reservoir and to understand the causes of cyanobacterial blooms. The amount of cyanobacteria is indicated by the concentration of chlorophyll-a. The suitability to use DYRESM-CAEDYM on Kranji reservoir is examined before relationships between chlorophyll-a and other parameters such as nutrients and thermal stratification are explored. Major findings suggest that inflow and discharge rates have an inverse relationship with chlorophyll-a and phosphorus availability is one factor that directly affect chlorophyll-a concentration in the reservoir. TN/TP ratio is also shown to be not suitable as an indication of cyanobacterial bloom for Kranji reservoir. Preliminary effects of stratification on chlorophyll-a is also simulated and the results show that stratification causes an increase in chlorophyll-a.